A study on warehouse management of REB: a case study of Central Warehouse, Dhaka - Sayeed, Md. Sakil Ibne (BRAC University, 2014)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2013.